2016
DOI: 10.1111/eci.12594
|View full text |Cite
|
Sign up to set email alerts
|

Heart acceleration and deceleration capacities associated with dilated cardiomyopathy

Abstract: Heart rate acceleration capacity and deceleration capacity are independent risk factors for DCM, and acceleration capacity is a predictive factor for heart failure exacerbation in patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…As we reported previously (Figure 1B) (Zou et al, 2016), a PRSA algorithm detects and quantifies quasi-periodic oscillations masked by non-periodic components, artifacts, and ectopic beats (Kantelhardt et al, 2007). We used this algorithm to analyze 24-h ambulatory electrocardiograms.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…As we reported previously (Figure 1B) (Zou et al, 2016), a PRSA algorithm detects and quantifies quasi-periodic oscillations masked by non-periodic components, artifacts, and ectopic beats (Kantelhardt et al, 2007). We used this algorithm to analyze 24-h ambulatory electrocardiograms.…”
Section: Methodssupporting
confidence: 54%
“…Using the PRSA technique, we could calculate heart rate acceleration capacity (AC) and deceleration capacity (DC) based on 24-h ambulatory electrocardiograms records. Researches revealed that the AC and DC are associated with mortality after myocardial infarction and heart failure stages in DCM patients with high predicting performance (Bauer et al, 2006; Hu et al, 2016; Zou et al, 2016). Assuming that AC and DC could reflect the sympathetic and parasympathetic nervous modulation in heart, we could learn the pathophysiological changes of autonomic nervous regulation in DCM from a new angle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lower HR was related to reversal of cardiac remodeling [14,35]. A recent report by Zou et al [36] noted that HR deceleration and acceleration capacities are independent risk factors for dilated cardiomyopathies. Moreover, HR acceleration may be a valuable HF exacerbation prognostic factor.…”
Section: Discussionmentioning
confidence: 97%
“…applied the PRSA algorithm in AC and DC of the heart rate 17 , more and more studies have found that AC and DC are related not only to physiological activity but also to a number of pathophysiological states. DC decreased gradually with age increase in normal population; 22 the magnitudes of DC and AC increased progressively as breathing frequency decreased; 28 lower DC of heart rate is a strong and independent predictor of 1-year mortality in patients with severe aortic stenosis undergoing transcatheter aortic valve implantation; 29 AC is positively associated with heart failure grade in patients with dilated cardiomyopathy; 16 lower DC assessed from short-term recordings is a strong and independent predictor of mortality and cardiovascular mortality after myocardial infarction 30 . These reports showed the complex role of ANS in the physiological and pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described 16 , a transthoracic echocardiographic examination was performed using a Sonos 5500 type Ultrasound machine (Philips, Best, Netherlands) with a 2.5 Hz transducer. The parameters measured with the M-mode technique included left ventricular end-diastolic, end-systolic and left atrial diameters.…”
Section: Methodsmentioning
confidence: 99%